2005
DOI: 10.13182/fst05-a694
|View full text |Cite
|
Sign up to set email alerts
|

The Toroidal Pump Limiter ALT-II in TEXTOR

Abstract: The Advanced Limiter Test (ALT) project is the focus of a fruitful and intense International Energy Agreement collaboration on TEXTOR. The pump limiter is a mechanical boundary that is laid out for taking the full heat load of TEXTOR, namely 8 MW (assuming 2 MW radiated power) for 10 s, and provides a pumping efficiency of at least 5% of the working gas. This layout is adopted from the requirements of a fusion reactor: It is mandatory to remove both the full power that is convected to the limiter or divertor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…At the same time, the 3D magnetic topology in the plasma edge a mixture of closed field lines inside of the island separatrix and open field lines of various magnetic connection length connecting form the island Xpoint region to the wall [46,61,62]) is likely to alter the coupling to the ALTII limiter blades as exhaust device. For details of the ALTII layout and the pumping geometry, please see figure 2 in [43]. This is assessed using 20% increase of the toroidally averaged neutral pressure in the ALTII pump ducts is measured.…”
Section: Impact Of the Magnetic Island On The Neutral Pressure Distri...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the 3D magnetic topology in the plasma edge a mixture of closed field lines inside of the island separatrix and open field lines of various magnetic connection length connecting form the island Xpoint region to the wall [46,61,62]) is likely to alter the coupling to the ALTII limiter blades as exhaust device. For details of the ALTII layout and the pumping geometry, please see figure 2 in [43]. This is assessed using 20% increase of the toroidally averaged neutral pressure in the ALTII pump ducts is measured.…”
Section: Impact Of the Magnetic Island On The Neutral Pressure Distri...mentioning
confidence: 99%
“…In order to approach this, we report on comparative experi ments at TEXTOR and LHD. TEXTOR is a medium size limiter tokamak with a circular plasma shape featuring the Advanced Limiter Test II device (ALTII) [42,43]. Dedicated studies of its exhaust capacities have shown that it is effi cient to exhaust hydrogen and also helium from both cir cular Lmode as well as radiative improved mode (RI mode) TEXTOR plasmas [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The position of the last closed flux surface (LCFS) is defined by the toroidal belt limiter ALT-II (Advanced Limiter Test II) [2]. ALT-II consists of 8 blades, each carrying 28 tiles ordered in two rows, with a total surface area of 3.4 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The position of the last closed flux surface (LCFS) is defined by the toroidal belt limiter ALT-II (Advanced Limiter Test II) [12]. ALT-II consists of 8 blades, each carrying 28 tiles ordered in two poloidal rows, with a total surface area of 3.4 m 2 ( Fig.…”
mentioning
confidence: 99%